Sports injury research (Oxford University Press, 2010)
With the increasing focus on tackling obesity and other lifestyle-related illnesses and conditions, participation in sports and physical activity is growing. The consequences are that injuries and unwanted side-effects of healthy activity are becoming major health problems. Prevention is crucial to health gain, both in the short-term (preventing immediate injury), and in the longer term (reducing the risk of recurrence and prolonged periods of impairment). Prevention follows 4 main steps: 1) the sports injury problem must be described in incidence and severity, 2) the etiological risk factors and mechanisms underlying the occurrence of injury are identified, 3) preventive methods that are likely to work can be developed and introduced, and 4) the effectiveness and cost-effectiveness of such measures are evaluated. This book follows these four steps to provide a comprehensive guide to the epidemiology and methodology involved in sports injury research. It includes detailed background on epidemiological methods employed in research on sports injuries, discusses key methodological issues, and teaches the reader to recognize the influence of the employed methodology on interpretations of study results. Theoretical knowledge is integrated with practical examples throughout. The book will be of value to all researchers and professionals, both clinicians and epidemiologists, in the field of sports medicine. The book has been written by leaders in the field of sports injury research and combines theoretical knowledge with practical examples, to assist the reader in placing theoretical knowledge in the right perspective. (oup-Verlagsinfo)